PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN DENGAN WORD OF MOUTH POSITIF SEBAGAI VARIABEL MEDIASI - Sumadi - (Universitas Slamet Riyadi, 2015)
The purpose of this study was to analyze the significance of the impact of service quality on positive word of mouth. Analyze the significance of the effect of quality of service and positive word of mouth to customer satisfaction. Analyze the significance of the effect service quality on customer satisfaction mediated by positive word of mouth. In conclusion, significance effect on service quality to positive word of mouth. Quality of service and positive word of mouth significance effect in the customer satisfaction. Positive word of mouth mediating effect of service quality on satisfaction. Keywords: service quality, customer satisfaction, positive word of mouth